Efeito da música na capacidade de caminhada de indivíduos claudicantes com doença arterial periférica: um estudo piloto - Ana Flávia Ferreira (2023)
Peripheral arterial disease (PAD) is characterized by the obstruction of blood flow in the lower limbs. Its risk factors are the same as other cardiovascular diseases, such as hyperlipidemia, hypertension, smoking, diabetes mellitus, and aging. Intermittent claudication (IC) is the classic symptom of PAD, characterized by pain in the buttocks, thighs, and calves during walking. IC is often considered a barrier to adherence to cardiovascular rehabilitation programs. The gold standard treatment is the performance of resistance and aerobic exercises at a moderate to maximum pain intensity, as well as participation in health education programs. Therefore, improving the adherence of individuals with PAD to cardiovascular rehabilitation programs should be an objective. In search of alternatives to enhance the performance of individuals with PAD during exercise, the use of music appears as a promising ergogenic resource. Music seems to be able to influence responses during physical exercise, acting as a resource capable of optimizing outcomes in both healthy individuals and those with a clinical condition. The primary objective of this dissertation was to evaluate the acute effect of music on walking capacity during treadmill testing in individuals with PAD. The secondary objectives were to assess hemodynamic responses, subjective perception of effort, and claudication symptoms under the effect of music during walking in individuals with PAD, to determine if there were differences in walking distance results based on different musical tempos, and to independently evaluate individuals who reported liking or disliking music. This was a pilot study conducted with individuals with PAD, aged ≥ 18 years, ankle-brachial index < 0.90 at rest, and without physical and cognitive conditions that would limit test performance. On the first day, a detailed anamnesis, evaluation with the MiniMental State Examination, and evaluation of sound identity (ISO) were performed, in addition to familiarization with the study instruments. On the second and third days, treadmill tests were conducted with and without music stimulation in a randomized order. In both tests, participants wore headphones and were accompanied by a second evaluator blinded to the presence or absence of the auditory stimulus. The results showed that the treadmill test with music had a 31% greater walking distance and duration compared to the test without music, but without statistical significance (p > 0.05). Secondary analyses showed that the final subjective perception of effort was higher in the music-enhanced test (p = 0.028). Individuals who reported liking music performed better in both tests but were also part of the younger age group. Treadmill tests with a predominance of medium musical tempos showed a 30% increase in walking distance without statistical significance. This dissertation confirmed that the use of music is a promising resource and demonstrated that medium tempo can be an option for choice in future clinical trials.